Physiological responses induced by phospholipase C isoform 5 upon heat stress in Arabidopsis thaliana - Annum, Nazish; Ahmed, Moddassir; Tester, Mark; Mukhtar, Zahid; Saeed, Nasir Ahmad (Frontiers in Plant Science, 2023)
Plant’s perception of heat stress involves several pathways and signaling molecules, such as phosphoinositide, which is derived from structural membrane lipids phosphatidylinositol. Phospholipase C (PLC) is well-known signaling enzyme containing many isoforms in different organisms. In the present study, Phospholipase C Isoform 5 (PLC5) was investigated for its role in thermotolerance in Arabidopsis thaliana. Two overexpressing lines and one knock-down mutant of PLC5 were first treated at a moderate temperature (37 ºC) and left for recovery. Then again exposed to a high temperature (45 ºC) to check the seedling viability and chlorophyll contents. Root behavior and changes in 32Pi labeled phospholipids were investigated after their exposure to high temperature. Overexpression of PLC5 (PLC5 OE) exhibited quick and better phenotypic recovery with bigger and greener leaves followed by chlorophyll contents as compared to wild type (Col-0) and PLC5 knock-down mutant in which seedling recovery has been compromised. PLC5 knock-down mutant illustrated well-developed root architecture at control conditions but stunted secondary roots under heat stress as compared to overexpressing PLC5 lines. Around a 2.3-fold increase in Phosphatidylinositol 4,5-bisphosphate level was observed in PLC5OE lines upon heat stress when compared with wild type and PLC5 knock-down mutant lines. A significant increase in Phosphatidylglycerol was also observed in PLC5OE lines as compared to Col-0 and PLC5 knock-down mutant lines. The results of the present study demonstrated that PLC5 overexpression contributes to heat stress tolerance while maintaining its photosynthetic activity and is also observed to be associated in primary and secondary root growth in Arabidopsis thaliana.